Studi Komparasi Konsep Pendidikan Islam Dalam Keluarga Abdurahman An-Nahlawi dan Zakiah Daradjat - Qosim, Andi Luqmanul; Safitry, Nurul Azmi (Universitas Islam Sultan Agung, 2021)
AbstractAs Muslim, parents hold important role in applying Islamic education to educate their children. This is done to strengthen children’s beliefs in Islam religion. However, in family education, many parents do not know the foundation, methods, and materials of Islamic education. The lack of understanding resulted in parents tend to use physical and psychological violence in educating their children. This situation raised concerns to Abdurrahman An-Nahlawi and Zakiah Daradjat. Both feels moved to conceptualize Islamic education in the family so that children from Muslim families can become ‘the complete person’ (insân kâmil). The comparative test of the two concepts shows that the differences in the basis, method, and material of the two can actually be an alternative for parents in applying education to their children. The outcome upon their children depend on the creativity of the parents in processing sources, methods, and materials in the concept of Islamic education from An-Nahlawi and Zakiah.Keywords: Islamic Education, Family, Parents, Child Abstrak Sudah sewajarnya sebagai umat Islam, para orang tua menerapkan pendidikan Islam dalam mendidik anak-anaknya. Hal ini dilakukan seiring untuk menguatkan keyakinan dalam beragama. Namun dalam pendidikan keluarga, banyak orang tua yang belum mengetahui landasan, metode maupun materi pendidikan Islam. Ketidaktahuan ini berdampak pada pola mendidik orang tua kepada anak dengan menggunakan kekerasan fisik maupun psikis. Keadaan ini mengundang keprihatinan bagi Abdurrahman An-Nahlawi dan Zakiah Daradjat. Keduanya merasa tergugah untuk mengkonsepkan pendidikan Islam dalam keluarga agar anak-anak dari keluarga muslim dapat menjadi insân kâmil di masa mendatang. Uji komparasi dari konsep keduanya menunjukkan bahwa perbedaan landasan, metode dan materi dari keduanya justru dapat menjadi alternatif bagi para orang tua dalam mengaplikasikan pendidikan terhadap anak-anaknya. Hasil terhadap anaknya tergantung pada kreatifitas para orang tua dalam mengolah sumber, metode dan materi dalam konsep pendidikan Islam dari An-Nahlawi dan Zakiah.Kata Kunci: Pendidikan Islam, Keluarga, Orang Tua, Anak